A phosphorus/boron-containing triazine-trione derivative endowing epoxy resin with excellent flame retardance - H. J. Duan; J. F. Cao; Y. S. Chen; J. S. Wang; S. Ji; H. R. Ma (eXPRESS Polymer Letters)
A novel flame retardant containing boron and phosphorus, based on triazine-trione sturcture (TDB) was successfully synthesized, via substitution and esterification reaction between 1,3,5-tris(2-hydroxyethyl)isocyanurate (THEIC), diphenyl phosphoryl chloride (DPCP) and boric acid (BA), and then blended into DGEBA to prepare flame-retardant composites. The structure of TDB was characterized by Fourier transform infrared (FTIR) spectra and nuclear magnetic resonance (NMR). The thermal and flame-retardant properties of epoxy thermosets were systematically investigated. The results showed that the Tg, T5% and Tmax values of EP samples were gradually decreased with the increasing content of TDB, while the char yields at 700 °C increased. With the introduction of 10 wt% TDB, the LOI value of the thermoset was 27.5%, and the UL-94 rating reached V-0. Furthermore, compared with pure EP, the peak heat release rate (pk-HRR) decreased by more than half, as well as the lower total heat release (THR) and total smoke production (TSP) were obtained. The flame retardant mechanism was studied by analyzing the char residue after cone calorimeter (CC) test and the pyrolysis products via scanning electronic microscopy (SEM), laser Raman spectroscopy (LRS), FTIR and Pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). It revealed that on account of the existence of triazine-trione structure and phosphorus/boron elements, the intumescent and compact phosphorus/boron-rich char layer was formed, meanwhile, the non-flammable gases and phosphorus-containing free radicals from triazine-trione and DPCP structure can develop the flame retardancy in the gas phase.